In Canada every system of oppression is organized around settler colonialism. - Hadley, Candida (Idle No More, 2020)
Keywords: amériques; approches et analyses; canada; capitalisme; cours; discours dominant; fem3100; militance; patriarcat; personnes marginalisées; premier cycle; protection de la terre; racisme; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Promenade sur Marx : du côté des héroïnes - Lefebvre-Faucher, Valérie (Micro RM, 2020)
Avez-vous remarqué ce personnage en marge du cadre, dont on ne nous raconte pas l’histoire? Une enquêtrice décide de suivre la piste des femmes entrevues dans les portraits de Marx. Ses antennes féministes remuent en direction de l’héritage marxien: tant de gloire virile recouvrant une pensée d’égalité, c’est louche. Quel risque courons-nous si nous nous intéressons aux femmes qui étaient là? Une simple promenade qui, au final, chamboule tout. Vous qui possédez Le petit Karl comme un catalogue d’outils à dégainer dans toutes les situations, que savez-vous de l’œuvre d’Eleanor Marx? De l’influence de Jenny ou de Laura Marx? Camarades, quelqu’un vous a-t-il parlé d’elles pendant ces nombreuses années d’université?
Keywords: approches et analyses; cours; discours dominant; fem5050; histoire et politique; inégalités; militance; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; écriture des femmes*

Empowerment as a disabled, black woman - Oliver, Kym; Abdullahi, Jumoke (2020)
The dynamic duo of Jumoke and Kym tackle the topic of empowerment and what that means for disabled, Black women. This was filmed as part of a TEDx talk at the University of Sussex in England. _______________________________________________________________________________________________ TRIPLE CRIPPLES was created by @TheKymOliver & @JayOnLife to provide a platform for & highlight the narratives of Black & non-Black Women, Femmes & Non-Binary people of colour, living with disabilities. We are here. We exist! We know the media and mainstream disability conversations would have you believe otherwise mega eye roll*... But guess what? WE GOTS THA INTERNETS, BITCHEZZZZ!!! Eat it. *put on shades and look cool at night ———————————————————————————————- JOIN US ON OUR JOURNEY! Hit the comments box! And if you or any women/femmes/non-binary people you know, would like to be a guest... Hit the DM’s! 🖤 Website: https://thetriplecripples.uk/ Twitter/Instagram: @TripleCripples Follow Jumoke: @JayOnLife Follow Kym: @TheKymOliver ———————————————————————————————- Track: “runaway” ~ K15 feat. AMA LIVE! Big Love to K15 for kindly letting us use his amazing music as our bedding track!!! Check out @k15music, support his sound, buy some vinyls and follow him on all platforms: Twitter: @K15music Facebook: @K15music Soundcloud: @K15 Bandcamp: @K15music
Keywords: 2000 à aujourd'hui; afrique; amériques; approches et analyses; capacitisme; caraïbes; corps; cours; discours dominant; empowerment; europe; fem3300; femmes* noires; invisibilité; militance; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques